Analisis Persepsi Kualitas Layanan Kapal Feri Penyeberangan Ujung-Kamal - Mohamad Djaelani; Didit Darmawan (Journal of Trends Economics and Accounting Research, 2021)
The transportation industry has developed along with infrastructure development in various regions. The concept of service quality becomes very important and is related to the transportation industry. In East Java there is the Suramadu Bridge which has had a setback impact on the Ujung-Kamal ferry crossing business which had previously experienced its heyday in its time. This study intends to analyze the quality of ferry services and determine the level of passenger satisfaction through analysis of the difference between expectations and perceptions of passengers. Data has been retrieved from the company's passengers during their journey. There were 102 respondents whose data were collected. Examination of the level of passenger satisfaction found that the criteria were at the stage of being quite satisfied even though they were not completely satisfied. This value means that there is an important task for the management company to further improve passenger satisfaction. Another finding is that the service quality variable (servqual) has a partial or simultaneous role to form the passenger satisfaction variable. In order to provide high quality service, ferry companies must immediately master the demands, desires and dreams